2015
DOI: 10.1007/s10815-015-0506-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of metformin on reproductive function in obese male rats induced by high-fat diet

Abstract: Purpose The study aims to elucidate the changes in testicular spermatogenic function in high-fat diet (HFD)-induced obese rats and to evaluate the protective effects of metformin intervention. Methods Male Sprague-Dawley rats (n=18) were randomly divided into a control group (standard diet), an HFD group, and a metformin group (HFD + metformin at 100 mg/kg, once daily by oral gavage). After 8 weeks, rats were euthanized, and the weights of body and testes were measured. Testis and epididymis were dissected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
60
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 24 publications
10
60
0
7
Order By: Relevance
“…This was supported by the reduction in the testicular weight and coefficient in the HFD group compared with the control group, which was consistent with the Yan et al's findings [33]. Furthermore, the decreased concentration, viability, motility, and morphology of sperm in HFD rats indicated poor sperm quality.…”
Section: Discussionsupporting
confidence: 89%
“…This was supported by the reduction in the testicular weight and coefficient in the HFD group compared with the control group, which was consistent with the Yan et al's findings [33]. Furthermore, the decreased concentration, viability, motility, and morphology of sperm in HFD rats indicated poor sperm quality.…”
Section: Discussionsupporting
confidence: 89%
“…Several papers are available, which report a significant decrease in testicular weight of rats fed with a HFD (Yan et al 2015, Gujjala et al 2016, beside those reporting no significant difference in testicular mass (Hu et al 2013, Campos-Silva et al 2015. A previous study (El-Desoky et al 2013) stated that administration of SP, suspended in water, by gavage for 60 consecutive days did not cause any significant difference in testis weights.…”
Section: Discussionmentioning
confidence: 99%
“…A PCNA immunohistochemistry study reported a significant decrease in cell proliferation in the testis of Wistar rats fed a HFD rich in saturated fatty acids (Campos-Silva et al 2015). In a previous study using TUNEL method, apoptotic index was reported to significantly increase in testis of rats fed a HFD (Yan et al 2015). In accordance with these studies, apoptotic index was significantly higher in HVO+CHL group (G4), and cell proliferation was significantly decreased in HVO (G2) and cholesterol (G3) groups in our study.…”
mentioning
confidence: 94%
“…Metformin may induce different effects depending on the age, stage of development, the metabolic status (insulin resistant or not), the species, dose and method of administration of the insulin sensitiser. Thus, there is data indicating that metformin administration in adult obese rats fed high-fat diet restores reproductive parameters (testosterone, E 2 , semen quality and testis weight; Yan et al 2015). In addition, there is a recent report of an increase in the percentage of intersex fish after metformin exposure during developmental stages at environmental doses, without clear effects on testosterone levels and gonad appearance (Niemuth et al 2015).…”
Section: Discussionmentioning
confidence: 99%